A gate-activated Pdse2 photodetector with a broadband detection from visible to mid-infrared region - Zhang, Xuran (Nanyang Technological University, 2022)
Radiations with different wavelength are widely existing in nature and human society. It has broad applications in microelectronics, medicine, military, and other civilian fields. Human eyes cannot directly observe ultraviolet radiation quantitively. Photodetectors refer to the devices that enable to convert incident light into electrical signals. Photodetectors as ultrasensitive and fast light sensors have a very wide utilization in the many aspects of the human society, such as the industry, military offense field, and our daily life.